Pemeriksaan Basil Tahan Asam dan Laju Endap Darah Sebagai Indikator Keberhasilan Pengobatan Penderita Tuberkulosis Paru di Puskesmas Singotrunan Banyuwangi - Nadiah Al Batati; Dinata Muthmainnata; Evy Ratnasari Ekawati; Setyo Dwi Santoso; Elsa Mega Suryani; Indra Adi Wira Prasetya (Jurnal SainHealth, 2023)
This research is based on Mycobacterium tuberculosis infection which can increase the value of erythrocyte sedimentation rate. Where the transmission of these bacteria through the respiratory tract is known as Droplet Infection. The purpose of this study was to find out the effect of one month tuberculosis treatment on the erythrocyte sedimentation rate (ESR) and acid fast bacilli (AFB) examination. This type of research is a laboratory observation study with an accidental sampling technique of 30 samples which was carried out at the Singotrunan Banyuwangi health center for 30 days. The results showed that out of 30 samples examined, it showed that there was an influence of ESR and acid fast bacilli examinations on Tuberculosis patients who had been treated for one month. The conclusion is that there is an influence on Tuberculosis patients on ESR and AFB examinations at the Singotrunan Banyuwangi Health Center. Keywords : Tuberculosis, ESR, AFB